Charakterystyka wybranych zmian prawa emerytalnego - Nerka, Arleta (Annales. Etyka w Życiu Gospodarczym, 2012)
The subject of this paper is to analyse the reconstruction of the pension system resulting from legislative changes introduced in 2011,the most important being the transfer of part of pension contributions from the open pension fund (OFE) to a newly set up special subaccountmanaged by the Social Insurance Institution, modifications in administrative regulation of open pension funds investment policyand introduction of tax incentives for making additional savings for retirement purposes.These transformations result from assumed financial goals such as reduction of public debt growth by reducing the cost of introducingthe second capital pillar in 1999. However, given the social importance of pension insurance the changes should be assessed againstassumptions of the pension reform of 1999 and constitutional principles.Key words: